Patient-Physician Interaction and Quality of Life in Recently Diagnosed Breast Cancer Patients - Kwan, Marilyn L. (2013)
INTRODUCTION: Few studies have explored how patient-physician interactions influence patients’ quality of life (QOL). In a prospective cohort study of 1,855 women diagnosed with invasive breast cancer in the Kaiser Permanente Northern California (KPNC) Medical Care Program from 2006 to 2011, we examined associations between patient-physician interactions during cancer treatment and QOL, overall and by racial/ethnic group. METHODS: Participants completed the Interpersonal Processes of Care (IPC) Survey at approximately eight months post-diagnosis to assess specific domains of the patient-physician interaction during the months after cancer diagnosis. Domains included: compassion, elicited concerns, explained results, decided together, lack of clarity, discrimination due to race/ethnicity, and disrespectful office staff. The Functional Assessment of Cancer Therapy-Breast Cancer (FACT-B) was completed concurrently to measure QOL. Linear regression models examined the association of IPC with QOL, first adjusting for patient covariates including age, race, clinical factors, and psychosocial measures and then for physician characteristics such as age, sex, race/ethnicity, and specialty. RESULTS: For all participants (n=1,855), IPC scores suggesting greater lack of clarity, discrimination due to race/ethnicity, and disrespectful office staff in patient-physician interactions were associated with lower QOL (p<0.01). IPC scores suggesting physicians demonstrating compassion, eliciting concerns, or explaining results were associated with higher QOL (p<0.01). Among Whites (n=1,306), only the associations with higher QOL remained. African Americans (n=110) who reported higher scores on physician compassion and elicited concerns had higher QOL, whereas higher scores for disrespectful office staff had lower QOL. No associations were observed among Asians (n=201) and Hispanics (n=186). After further adjustment for physician factors, the associations among Whites remained whereas those among African Americans disappeared. CONCLUSION: In the breast cancer treatment setting, characteristics of the patient-physician interaction as perceived by the patient are associated with QOL, yet were not specific to patient race/ethnicity.